Characteristics of cloud cluster over the steep southern slopes of the Himalayas observed by CloudSat. (28th February 2017) - Chen, Yilun; Fu, Yunfei; Xian, Tao; Pan, Xiao
ABSRACT: A cloud cluster (CC) dataset is presented using CloudSat Cloud Profile Radar (CPR) observations from June to August, between 2006 and 2010. The CCs were defined by grouping contiguous cloud pixels using a defined criteria, including reflectivity, 'cloud mask', and topographic information. The characteristics of identified CCs were then analysed. Based on the complex topography of the southern Himalayas, four adjacent regions were selected, including the flat Gangetic Plains (FGP), the foothills of the Himalayas (FHH), the steep slope of the southern Himalayas (SSSH), and the Himalayan‐Tibetan Plateau (HTPT). The characteristics of the CCs in the four regions were different, and the distribution of the cloud‐top height gradually changed from bimodal (3 and 15 km) over the FGP and FHH, to unimodal (7–9 km) over the HTPT. From the plain to the Plateau, the average cloud‐top height and cloud‐base height increased after an initial decrease. The maximum reflectivity increased from −6 (plain) to 2 dBZ (slope areas), and then decreased to −2 dBZ (Plateau), which suggests that the CCs may produce precipitation on the slope. Maximum CCs occurred over the FHH. The characteristics of the CCs also showed semidiurnal variation, which may have been affected by the variation of the monsoon and the circulation over the mountain valley. According to the physical principles of the cloud‐type definitions from ISCCP, high‐level cirrus, deep convective CCs, and mid‐ to low‐level CCs were categorized. As the elevation increased, the cloud‐top height of the mid‐ to low‐level CCs also significantly increased to 8 km, whereas the cloud‐top height of the high‐level cirrus clouds decreased. Our results suggest that the different characteristics of CCs may be caused by a strong upward motion interacting with the terrain of the Himalayas.